2020
DOI: 10.3390/v12121439
|View full text |Cite
|
Sign up to set email alerts
|

Re-Invasion of H5N8 High Pathogenicity Avian Influenza Virus Clade 2.3.4.4b in Hokkaido, Japan, 2020

Abstract: Global dispersion of high pathogenicity avian influenza (HPAI), especially that caused by H5 clade 2.3.4.4, has threatened poultry industries and, potentially, human health. An HPAI virus, A/northern pintail/Hokkaido/M13/2020 (H5N8) (NP/Hok/20) belonging to clade 2.3.4.4b, was isolated from a fecal sample collected at a lake in Hokkaido, Japan where migratory birds rested, October 2020. In the phylogenetic trees of all eight gene segments, NP/Hok/20 fell into in the cluster of European isolates in 2020, but wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…All the isolates sequenced in this study possessed multibasic amino acid sequences (PLREKRRKR*GLF (n = 65) and PLIEKRRKR*GLF (n = 2)) in the cleavage site of the HA gene, indicating a high-pathogenicity phenotype in chickens (Supplementary Table S1). The H5N8 clade 2.3.4.4b viruses identified in late October 2020 from a fecal sample of a mandarin duck collected in Chungnam province, South Korea, and a fecal sample of a northern pintail collected in Hokkaido, Japan, also had the PLREKRRKR*GLF cleavage site motif [20,30]. Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the isolates sequenced in this study possessed multibasic amino acid sequences (PLREKRRKR*GLF (n = 65) and PLIEKRRKR*GLF (n = 2)) in the cleavage site of the HA gene, indicating a high-pathogenicity phenotype in chickens (Supplementary Table S1). The H5N8 clade 2.3.4.4b viruses identified in late October 2020 from a fecal sample of a mandarin duck collected in Chungnam province, South Korea, and a fecal sample of a northern pintail collected in Hokkaido, Japan, also had the PLREKRRKR*GLF cleavage site motif [20,30]. Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Table S1). The H5N8 clade 2.3.4.4b viruses identified in late October 2020 from a fecal sample of a mandarin duck collected in Chungnam province, South Korea, and a fecal sample of a northern pintail collected in Hokkaido, Japan, also had the PLREKRRKR*GLF cleavage site motif [20,30]. The phylogenetic analysis of the HA gene of the HPAI H5N8 viruses detected in South Korea showed that all the isolates belong to H5 clade 2.3.4.4b and form two distinct genetic groups (G1 and G2), suggesting separate introductions of two genetically distinct H5N8 clade 2.3.4.4 viruses ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…On 5 November 2020, an outbreak due to an H5N8 HPAIV was confirmed at an egg-hen farm where 300,000 of layer were raised in cages in Kagawa prefecture (western Japan). Eleven days before the outbreak (i.e., 24 October 2020), another H5N8 isolate, A/northern pintail/Hokkaido/M13/2020 [ 4 ], was detected in feces collected in Hokkaido prefecture (northern Japan). In addition, since the end of August 2020, H5N8 HPAIVs have been detected in wild bird and poultry species in Russia, Kazakhstan, Israel, European Union countries, and South Korea [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the winter of 2019/2020, H5N8 HPAIVs belonging to clade 2.3.4.4b caused outbreaks in wild and domestic birds in Europe [ 8 ]. Similarly, in the winter of 2020/2021, genetically similar H5N8 HPAIVs from clade 2.3.4.4b were disseminated not only in European countries, but also in South Korea and Japan [ 9 , 10 ], which is most likely due to the migration of wild aquatic birds that are considered natural reservoirs of avian influenza viruses (AIVs) [ 11 ], as suggested in previous studies on the dissemination of H5N8 HPAIVs [ 3 , 4 , 5 , 6 ]. Here, we describe the isolation of two H5N8 HPAIVs clade 2.3.4.4b from a fecal sample of falcated ducks ( Anas falcata ) and an environmental water sample collected in Japan in November 2020.…”
mentioning
confidence: 99%
“…All eight gene segments from A/falcated duck/KU-d3/2020 (H5N8) showed high similarities (99.34–99.90%) to their counterparts from two H5N8 HPAIVs of clade 2.3.4.4b isolated in East Asia in October 2020, namely A/Mandarin duck/Korea/H242/2020 (H5N8) [ 9 ] and A/northern pintail/Hokkaido/M13/2020 (H5N8) [ 10 ]. Although the gene segments from A/falcated duck/KU-d3/2020 (H5N8) also showed high similarity to European poultry isolates from the winter of 2019/2020 [ 21 ], they were less similar than those against the Asian isolates.…”
mentioning
confidence: 99%